Peroxisomal Acyl-CoA Oxidase Type 1: Anti-Inflammatory and Anti-Aging Properties with a Special Emphasis on Studies with LPS and Argan Oil as a Model Transposable to Aging - Vamecq, Joseph (Oxid Med Cell Longev, 2018)
To clarify appropriateness of current claims for health and wellness virtues of argan oil, studies were conducted in inflammatory states. LPS induces inflammation with reduction of PGC1-α signaling and energy metabolism. Argan oil protected the liver against LPS toxicity and interestingly enough preservation of peroxisomal acyl-CoA oxidase type 1 (ACOX1) activity against depression by LPS. This model of LPS-driven toxicity circumvented by argan oil along with a key anti-inflammatory role attributed to ACOX1 has been here transposed to model aging. This view is consistent with known physiological role of ACOX1 in yielding precursors of specialized proresolving mediators (SPM) and with characteristics of aging and related disorders including reduced PGC1-α function and improvement by strategies rising ACOX1 (via hormonal gut FGF19 and nordihydroguaiaretic acid in metabolic syndrome and diabetes conditions) and SPM (neurodegenerative disorders, atherosclerosis, and stroke). Delay of aging to resolve inflammation results from altered production of SPM, SPM improving most aging disorders. The strategic metabolic place of ACOX1, upstream of SPM biosynthesis, along with ability of ACOX1 preservation/induction and SPM to improve aging-related disorders and known association of aging with drop in ACOX1 and SPM, all converge to conclude that ACOX1 represents a previously unsuspected and currently emerging antiaging protein.